Cover Picture: Experimental Polymer Mechanochemistry and its Interpretational Frameworks (ChemPhysChem 11/2017). Issue 11 (29th May 2017) - Akbulatov, Sergey; Boulatov, Roman
Abstract : The Front Cover picture illustrates the central idea of mechanochemistry: distorting a polymer can cause its monomers to react in a way that is exceedingly unlikely without mechanical load. Among the simplest, but probably most widespread examples of such load‐induced chemistry is homolysis of bonds in vulcanized rubber. More information can be found in the Review by S. Akbulatov and R. Boulatov onpage 1422 in Issue 11, 2017 (DOI:10.1002/cphc.201601354 ).